Pricing in the sharing economy - Schäfers, Tobias; Benoit, Sabine (Elgar Encyclopedia of Pricing)
The emergence of the sharing economy has transformed consumption patterns, shifting the focus from ownership to access-based models. This entry outlines the diverse nature of sharing economy business models, specifically contrasting dyadic access-based services and peer-to-peer platforms and describes the trends underlying the proliferation of such business models. Moreover, a structured approach for understanding the particularities of pricing in the sharing economy is provided. The factors influencing pricing strategies within these models are discussed, namely the number of actors involved, the actors responsible for deciding on prices, and the purpose of pricing. The entry also provides a framework that identifies different pricing approaches used in the sharing economy, ranging from static to dynamic and usage-dependent to usage-independent. This analysis underscores the complexities inherent in pricing strategies within the sharing economy, offering insights into the multifaceted nature of pricing these innovative services.